Inkorporasi Kromium oleh Fungi Ganoderma lucidum dengan Limbah Industri Kelapa Sawit Sebagai Substrat - F Agustin; T Toharmat; D Evvyernie; D Taniwiryo; S. Tarigan; I Prihantono (Media Peternakan, 2010)
The aim of this study was to determine the effective Cr (chromium) level for Ganoderma lucidum growth in solid state fermentation of oil palm by-product. Treatments were combination of Cr level (0, 500, 1000, 1500, 2000, 25000, and 3000 ppm) and fermentation time (0, 2, 4, 6, and 8 weeks).  The treatments were allocated in a factorial 7x5 of complete randomized design with four replications. Inoculant of G. lucidum was grown in potato dextrosa agar (PDA) medium for 10 days and then innoculated to substrate which have been autoclaved and mixed with CrCl3.6H2O. The moisture of substrate was maintained at 65%. Growth media of G. lucidum was diluted with aquades and the supernatant was analysed for its Cr content.  The result showed that the addition of Cr up to 3000 ppm into the medium stimulated the G. lucidum growth in all experimental condition. The Cr ions were incorporated into the media and G. lucidum cells during fermentation. Incorporation of chromium by G. lucidum was higher in oil palm by-product substrate with 3000 ppm Cr than the others. It is concluded that Cr can be incorporated into the G. lucidum cells during fermentation. The effective level of Cr for G. lucidum growth was 3000 ppm with efficiency of Cr incorporation 68.23% in 8 weeks fermentation and chromium in protein of fermentation product was 12.01%. Key words: chromium, Ganoderma lucidum, oil palm by-product